(untitled) (Journal of Scientific Research, 2020)
Present work includes synthesis of five NH-analogues of ciprofloxacin, 2-6 have been prepared to find out their medicinal assessment, for instance, antibacterial, antifungal, and cytotoxicity. The structure of the analogues has been confirmed by FT- IR, 1H-NMR, 13C-NMR, mass spectral data and elemental analysis. The compounds were screened for their antimicrobial activities by the disc diffusion method. Cytotoxicity was also tested against brine shrimp lethality assay. The antimicrobial activity of the analogues compared with the parent was evaluated against three Gram-positive, five Gram-negative bacterial strains and three fungi. The synthesized compounds showed diverse antimicrobial profile among which derivatives, 2 and 3 possessed enhanced activity in contrast to the ciprofloxacin. Additionally, unlike ciprofloxacin, most of the derivatives were also found to show antifungal activity against Candida albicans. Regarding cytotoxicity, most of the derivatives exhibited better cytotoxic activity than ciprofloxacin.